Sistem Informasi Manajemen Pelayanan Permohonan Surat Keterangan dan Surat Pernyataan (SIM-PPSKP) - Sinta Rukiastiandari; Teo Filus Simanjuntak; Hamdun Sulaiman Hamdun (IMTechno: Journal of Industrial Management and Technology, 2021)
The government as an actor in providing public services needed by the community is responsible for providing the best service and continuously striving to improve the quality of public services. Service success can be measured by community satisfaction in terms of services provided by public service providers. Therefore the public service provider must continue to strive and innovate so that the quality of public services becomes even better. For that reason, in building a system design that aims to improve public services, i use the prototype method. The application of the system is very important for the information system developer to support the success of the information system whether it is going according to plan and in accordance with the wishes of the user. The prototype was created with the aim of providing equal perception and initial understanding in the basic process of the system to be designed, so that good communication will be established between the designer and the user of the system. With the existence of a public service management information system so that it can ease the duties and obligations of public service providers. This can increase public satisfaction in public services and can support the quality of public services to be the best